SCREENING OF WHEAT (TRITICUM AESTIVUM L.) CULTIVARS FOR SALINE CONDITIONS UNDER IRRIGATED ARID ENVIRONMENT - Khan, Muhammad Aslam; Hussain, Nazim; Abid, Muhammad; Imran, Tahir (Journal of Research (Science), 2004)
Eight wheat cultivars were evaluated for yield and yield components under saline conditions of irrigated arid environment of Multan. The cultivars comprised: Manthar-3, Panjnad-1, BWP-2000, Inqlab-91, Iqbal-2000, SARC-1, BWP-97 and Darawar-97. The cultivar Punjnad-1 produced more tillers than all the other genotypes. But this cultivar could not maintain its position. In production of spikes, filled spikelets, 1000-grain weight, grain yield and harvest index, the cultivar Punjnad-1 was among the cultivars showing poor performance. This indicted that the existence of excessive tillers was drain to wheat plant reserves. On the basis of grain yield the cultivars SARC-1 and Iqbal-2000 were found relatively salt tolerant. The cultivars Manthar-3, Darawar-97, Panjnad-1, BWP-2000, BWP-97 and Inqlab-91 were found relatively less tolerant to salinity. The cultivars Iqbal-2000, SARC-1, Panjnad-1 and BWP-97 performed better in biological yield. The cultivars BWP-2000 and SARC-1 showed statistically higher values of harvest index among the wheat cultivars tested under saline conditions. The wheat cultivars having excessive tillering capacity should be avoided to grow in salt affected areas. Future breeding efforts in the salt affected areas should focus on wheat cultivars having balanced vegetative growth.